NEUROSCIENCE AND TEACHER TRAINING: CONTRIBUTIONS TO TEACHING AND LEARNING - Paiva, Azimavete de Sousa; Nogueira, Teresinha de Jesus A. Magalhães; Ramos, Sandra Lima de Vasconcelos; Felix, Mirian de Sousa Paiva; Faria, Carolina Brum (Seven Editora, 2026)
Given the contemporary challenges in education and the need for pedagogical practices based on scientific evidence, understanding how development and learning processes occur has been a major challenge. In this sense, Neuroscience presents its advances, contributing significantly to education. It is based on the premise that learning involves the integration of cognitive, emotional, and biological processes, with learning resulting from brain function articulated with attention, memory, emotion, and executive functions—central aspects for teaching and learning. Therefore, this study aims to analyze the contributions of neuroscience to the teaching and learning process, focusing on teacher training courses (initial training - Bachelor’s Degree in Pedagogy). It is a qualitative research study, developed through an analytical-integrative approach, in which content analysis of articles, books, and legal documents, such as CNE/CP Resolution No. 4/2024 and the Pedagogical Projects of the Courses, was carried out. Thus, a sample of two public universities (University of Brasília – UnB, and Federal University of Piauí – UFPI) was presented. The analysis concludes that the systematic integration of Neuroscience and Education is indispensable for improving pedagogical practices and promoting reflective, inclusive, and evidence-based teacher training. However, the analyzed course plans revealed that these institutions do not offer a specific Neuroscience course as a curricular component. Nevertheless, the courses include some subjects that have relationships, similarities, or complementary content to the knowledge addressed by Neuroscience.